New syllabus primary mathematics 4th 2nd edition - Dr Yee , Foong Pui (Karachi : Oxford University Press ., 2024)
New Syllabus Primary Mathematics (NSPM) is a series of textbooks and workbooks specially written to reflect a student-centred approach, which serves to engage pupils so that they have a solid foundation in Mathematics. This series meets the objectives of Pakistan Single National Curriculum 2020.
Keywords: Mathematics - Textbook; Oxford Matthematics - Textbook